School Fees Payment Accounting Management System - Afzan, Ahmad (2012)
School Fees Payment and Accounting Management System was developed to manage the fees payment that included PIBG fees, School fees and Hostel fees and managing school accounting record. Current practice use manual fees form to manage fees payment taken by teacher and using book accounting record to record all debit and credit for every month. This methods burden staff and teacher who want to manage fees payment and accounting record in manual way. SFPAMS was the solution to this problem. One of the upgrades is easing the process of by auto calculation fees payment. This system can help teacher to manage the fees payment because one of the objective to archive. Therefore, this system will be very helpful and can make the management of school fees payment and accounting record run smoothly. SFPAMS is develop by using Adobe Dreamweaver CS4 and Xamp Server